Effect of activation conditions on the pinang frond based activated carbon performance in dyes removal - Ahmad, Mohd Azhar (2014)
The production of activated carbon from agriculture waste offers both economical and environmental advantages. This study aims to prepare a novel pinang frond based activated carbon (PFAC) using a single-step physical activation method for removal of methylene blue (MB) and remazol brilliant blue R (RBBR) dyes from aqueous solution. The PFAC was produced at various activation conditions; i.e. activation temperature (600-900oC), activation time (1-7 hours) and CO2 flow rate (150-600 mL/min). All PFAC samples prepared have large surface area (<576 m2/g) and consist of pore in mesopore region. The experimental design results obtained via face centered composite design (FCCD) revealed that activation temperature, activation time and CO2 flow rate were important variables that influence the dyes removal performance by PFAC. The optimum conditions obtained for preparing PFAC were 867°C, 6.0 hour and 476 mL/min for activation temperature, activation time and CO2 flow rate, respectively. This optimum sample gave high surface area of 992.0 m2/g, pore volume of 0.551 mL/g and fixed carbon content of 80.24%. MB and RBBR removal of 96.8% and 76.4%, respectively were achieved by using this sample. Adsorption equilibrium and kinetic data of MB adsorption by PFAC were fitted well with Langmuir isotherm and pseudo-first-order kinetic model, respectively. On the other hand, the adsorption equilibrium and kinetic data of RBBR by PFAC were fitted well with Freundlich isotherm and the pseudo-second-order kinetic model, respectively.